Prophylactic central neck dissection and local recurrence in papillary thyroid microcarcinoma: a meta-analysis, - Su,Hui (2019)
Abstract Introduction: For papillary thyroid microcarcinoma patients, the reported incidence of lymph node metastasis is as high as 40%, and these occur mainly in the central compartment of the neck. Because these metastases are difficult to detect using ultrasonography preoperatively, some authors advocate routine central neck dissection in papillary thyroid microcarcinoma patients at the time of initial thyroidectomy. Objective: To evaluate whether prophylactic central neck dissection can decrease the local recurrence rate of papillary thyroid microcarcinoma after thyroidectomy. Methods: The publicly available literature published from January 1990 to December 2017 concerning thyroidectomy plus prophylactic central neck dissection versus thyroidectomy for papillary thyroid microcarcinoma was retrieved by searching the national and international online databases. A meta-analysis was performed after the data extraction process. Results: Four studies were finally included with a total of 727 patients, of whom, 366 cases underwent thyroidectomy plus prophylactic central neck dissection and 361 cases received thyroidectomy only. As shown by the meta-analysis results, the recurrence rates in cases of thyroidectomy plus prophylactic central neck dissection were approximately 1.91% and were significantly lower than those with thyroidectomy only (OR = 0.24, 95% CI [0.10, 0.56], p = 0.0009). Conclusion: For patients with papillary thyroid microcarcinoma, thyroidectomy plus prophylactic central neck dissection is a safe and efficient procedure and it results in lower recurrence rate. Since the evidences are of low quality (non-randomized studies), further randomized trials are needed.